PENGARUH CORPORATE SOSIAL RESPONSIBILITY, UKURAN PERUSAHAAN DAN MANAJEMEN LABA TERHADAP AGRESIVITAS PAJAK - Hanum, Ayu Noviani; Ria, Anan Fiq; Kristiana, Ida (Journal of Industrial Engineering & Management Research, 2023)
Abstract The purpose of this study is to examine the effect of corporate social responsibility, company size and earnings management on tax aggressiveness in coal & metal mineral sub-sector mining companies listed on the Indonesia Stock Exchange on the period 2016-2021. The sampling technique was purposive sampling and 10 samples were obtained which were accessed through the official idx.co.id account in the form of annual financial reports. The method of analysis is using multiple linear analysis. As for the data processing using the IBM SPSS Statistics 16 program. The results of this study indicate that (1). Corporate social responsibility has a negative on tax aggressiveness (2). Firm size has a negative on tax aggressiveness (3). Earnings management has no effect significant on tax aggressiveness. The determinant coefficient value of R Square is 0,248 (24,8%). This means that the variables corporate social responsibility, company size and earnings management are able to explain the tax aggressiveness of 24,8% and the remaining 75,2% is influenced by other factors or variables.